Can Porites spp. corals be used as a bio-indicator for sediment stress on coral reefs?. (November 2019) - Precht, William F.
Abstract: Bessell-Browne et al. (2017) published a paper where they proposed using mounding Porites spp. corals from Western Australia as a bio-indicator of sediment stress on coral reefs. They based their interpretations on results obtained during the monitoring of a capital dredging program coupled with laboratory sediment dousing experiments. They stated that because these Porites species generate mucous sheets in response to sediment loading, they could be used as an early warning indicator of sediment stress adjacent to sensitive coral resources. While their results are compelling, there are several confounding issues that arise questioning the wide-scale application and use of Porites spp. corals as bio-indicators. Using examples of Porites species from both the Indo-Pacific and Caribbean, I detail a number of contrary results that reveal that mucous sheet development is most likely attributed to mucus production and subsequent mucus sloughing that are cued to an endogenous lunar cycle (approximately 28 days in duration) and not necessarily as a direct strategy to protect the coral tissue from harm due to sediment stress. While the mucous sheet becomes fouled with sediment during the cycle, the amount of sediment observed may not be a response to the level of sediment stress, but where in the 28-day cycle the mucous sheet is observed. Thus, depending on when you observe the colony (early, middle or late in the 28-day cycle) the level of purported sediment impact would be highly variable. This variability leads to an unacceptably high rate of both Type-I and Type-II statistical errors. Because of the cyclical, endogenous nature of mucus production in many Porites spp., extreme caution should be employed before using these species to infer the level of sediment impact associated with dredging projects or their use as a predictive tool of sediment stress on coral reefs.